Knee and shoulder strength ratios in female karate athletes: age-related differences - Trajkovic, N.; Madic, D.; Maksimovic, N.; Milosevic, Z.; Obradovic, B.; Trivic, T.; Drapsin, M.; Drid, P. (Medicina dello Sport, 2019)
BACKGROUND: Using isokinetic testing in order to detect strength ratios represents reliable and reproducible measurements which can be used for injury prevention. This study aims to investigate and compare muscle imbalances in female karate athletes of different age groups. METHODS: The study sample consisted of three groups: 10 cadet (mean age: 15.00±0.81 years), 10 junior (mean age: 16.87±0.99 years), and 10 senior (mean age: 21.25±2.76 year) female karate athletes. The following isokinetic parameters were gathered: Ratio of right/left leg extensor force, ratio of right/left leg flexor force, ratio of right leg hamstring/quadriceps, ratio of left leg hamstring/quadriceps, ratio of right/left shoulder internal rotation, ratio of right/left shoulder external rotation, ratio of internal/external rotation in the right shoulder, and ratio of internal/external rotation in the left shoulder. RESULTS: The ratio of extensor and flexor muscles of the left and right leg in female karate athletes of different ages did not show statistically significant differences between groups (P>0.05). The hamstring/quadriceps ratio of the left leg in female karate athletes showed statistically significant differences (P<0.05) and high effect size (22%) between groups, indicating significantly higher results in senior than in junior athletes. The ratio of internal and external rotation of the right/left shoulder in female karate athletes of different ages did not show statistically significant differences between the groups (P>0.05). CONCLUSIONS: The results indicate that this group of karate athletes may have demonstrated sport-specific adaptations in certain strength measurements, but they showed no increased risk for knee injury.